An investigation on the operation of mechanical car park system in Kuala Lumpur / Mohd Norfikri Rosdi - Rosdi, Mohd Norfikri (Faculty of Architecture, Planning and Surveying, 2013)
The central business district of Kuala Lumpur experiences the highest level of traffic congestion in Malaysia. This is due to the insufficient parking space for the car owner. Therefore the implementation of Mechanical car park system that able to provide more parking space should be the solution to overcome the problem. This paper presents a study on an investigation on the operation of mechanical car park system in Kuala Lumpur. The aims of the study are to evaluate the present operational activities of mechanical car park system in the Kuala Lumpur and to recommend improvements on the activity. The data collection is made base on the distribution of questionnaire at the case study that been conducted. From the study that been done, it shown that the implement able to overcome the insufficient parking space in the building.